Comparative Study of Welding Material Elasticity with the SMAW Process for 2G Positions Between Before and After Using Welding Machines with Augmented Reality Technology - Arief Syarifuddin; Erdina Arianti; Kusnindar Priohutomo; Rosi Dwi Yulfani; Berlian Arswendo Adietya; Aurista Miftahatul Ilmah; Taufan Prasetyo (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
The high cost of certification and the low pass percentage in welding certification are common issues for beginner welders. The use of Augmented Reality (AR) technology is expected to solve these issues. The results of the penetrant, bending, and tensile tests showed that the welder who had used the AR welding machine produced better welding specimens than before they practiced using the AR welding machine. The penetrant test after beginner welder practiced using the AR welding machine produces rounded defects with a defect size of 1,44 mm (accepted by ASME Section V), whereas before they practiced using the AR welding machine it produces defects that cannot be accepted by the criteria. The maximum open discontinuity length in the bending test on the welded specimen after welder practiced using the AR welding machine is 2,90 mm (accepted by ASME Section IX), whereas the bending test before welder practiced using the AR welding machine is not accepted by the citeria. The tensile test results after welder practiced using the AR welding machine were 410,00 and 455,66 N/mm2 for the maximum tensile stress. This value exceeds the minimum tensile strength of SA-36 carbon steel, which is 400 N/mm2. When compared to the specimen before the welder practiced using the AR welding machine, the modulus of elasticity produced after the welder practiced using the AR welding machine is also smaller, indicating that the material has better elasticity. Based on the results of the tests, it can be seen that the AR welding machine can be used for the implementation of competency certification because the quality of the weld results is better, there are fewer risks (sparks, eye irritation, and burns), and the use of welding consumables is reduced